Factors influencing the financial satisfaction of CSE investors in Jaffna district - Luxan, K.; Kengatharan, L. (University of Jaffna, 2020)
Financial satisfaction results from a form of one's behavior that relates to how these individuals manage their income to meet their financial needs. Financial demand is said to be successful if it can meet individual consumption's short-term and long-term needs without any shortcomings. This study aims to find out the relationship between Financial Behavior, Financial Knowledge, Financial Attitude, with Financial Satisfaction. Colombo Stock Exchange investors living in Jaffna district have been considered for this study, and convenient sampling was used to select the participants of this study. Primary data were collected using a questionnaire and which were collected from 55 individual investors. Cronbach's Alpha was used to measure the reliability of the variables. Correlation and regression analysis were used for the data analysis. The study's outcome revealed that there wasa significant positive relationship of financial behavior, financial knowledge, and financial attitude with financial satisfaction. Future researchers are expected to consider more variables that may affect the financial satisfaction and accommodate more respondents to generalize the findings
Keywords: financial attitude on financial satisfaction; financial behavior; financial knowledge